Institución educativa rural Puyana con enfoque agropecuario en el Municipio de Lebrija Santander. (2023)
The objective of this work was to design an architectural project of school infrastructure with an agricultural approach in the educational institution Llanadas, Puyana rural school in the municipality of Lebrija, Santander. For this purpose, it used a mixed methodology that integrates qualitative methods for the subjective understanding of the pedagogical and social processes, and a quantitative method that allows the description of the information in statistical data